THE EFFECT OF LEADERSHIP STYLE, WORK MOTIVATION, WORK DISCIPLINE, COMPETENCE AND WORK ENVIRONMENT ON POLICE PERSONNEL PERFORMANCE (PROCEEDING OF INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDY, 2025)
The purpose of this study was to analyze the influence of leadership style on personnel performance, the influence of work motivation on personnel performance, the influence of work discipline on personnel performance, the influence of competence on personnel performance, and to analyze the influence of leadership style, work motivation, work discipline, competence, and work environment simultaneously on personnel performance. The population of this study was Police personnel at the Directorate of General Crimes of the Riau Islands Police, totaling 292 people. The sample consisted of 168 respondents. The sampling technique used simple random sampling, with the Slovin formula. Data analysis used multiple regression and hypothesis testing using SPSS. The results of this study are: leadership style has a positive and significant effect on personnel performance, work motivation has a positive and significant effect on personnel performance, work discipline has a positive and significant effect on personnel performance, competence has a positive and significant effect on personnel performance, and leadership style, work motivation, work discipline, competence, and work environment simultaneously have a positive and significant effect on personnel performance.